2020
DOI: 10.1177/1362361320918745
|View full text |Cite
|
Sign up to set email alerts
|

Motor atypicalities in infancy are associated with general developmental level at 2 years, but not autistic symptoms

Abstract: Atypical motor development has frequently been reported in infants at elevated likelihood for autism spectrum disorder. However, no previous study has used detailed motion capture technology to compare infant siblings of children with autism spectrum disorder and infant siblings with no familial history of autism spectrum disorder. We investigated reaching movements during an interceptive action task in 10-month-old infants using kinematic data with high spatiotemporal resolution. The results indicated that se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…Several early motor measures were different in 39 HR infants in comparison with 19 controls. However, they were not related to autistic symptoms at 2 years, but to the following non-social, general development [ 51 ]. Other specific manual motor behaviors have been considered in HR individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Several early motor measures were different in 39 HR infants in comparison with 19 controls. However, they were not related to autistic symptoms at 2 years, but to the following non-social, general development [ 51 ]. Other specific manual motor behaviors have been considered in HR individuals.…”
Section: Resultsmentioning
confidence: 99%
“…This is certified by classical studies in the literature 15,16 and by the introduction in the DSM-5 of motor functioning atypicalities as an associated feature of ASD (even if -notably -they are not diagnostic criteria for ASD, see 17 ). It is also true that recent literature exploring motor functioning in infancy and childhood has not found a general consensus in ascertaining motor dysfunctions in ASD, but instead describes a complex picture of similarities and differences as compared to neurotypical controls [18][19][20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…Since the model including Mullen scores did not explain the data better than the model without this predictor, we do not see evidence that differences in noise in the sensory and motor systems between the two groups influenced their performance on the task. This could be more directly analysed in future studies by recording motion tracking during the task, a method which has recently shown interesting insights into the development of autism and neurodevelopmental disorders (Achermann, Nyström, Bölte & Falck-Ytter, 2020;Caruso et al, 2020).…”
Section: Discussionmentioning
confidence: 99%